From exception to normalcy: The United States and the war on terrorism - Johannes Thimm (Stiftung Wissenschaft und Politik (SWP), 2018)
The war on terrorism waged by the United States is in its 17th year. To a large extent, it has defined three very different presidencies and no end is in sight. In the time since the terrorist attacks of September 11, 2001, the initial shock has gradually given way to a new normalcy. The time seems right to assess the US's approach to combating terrorism - an assessment this study attempts to provide. A key finding of this report is that the global war on terror is not only continuing, but that it is also becoming increasingly difficult to end. What began as a secret war is now firmly established US policy, both legally and institutionally. In the early years of the global war on terror, US methods were strongly criticized by Europe's governments. This criticism has now largely ceased. Detention without a trial, targeted killings, mass surveillance - all of this is at least tolerated, and in some cases even supported. This development is problematic in several respects. Its consequences include the systematic erosion of human and civil rights; the concentration of decision-making power in the hands of the executive at the expense of the separation of powers principle; and the expansion of the national security state. Since victory is unlikely, the question of whether to continue supporting the United States on its present course is all the more urgent.
Keywords: 320